Reviewer acknowledgement - Catena, Fausto (BioMed Central, 2014)
CONTRIBUTING REVIEWERS: The World Journal of Emergency Surgery—which received its first Impact Factor in 2013—is extremely grateful for the time, hard work and support of its highly-qualified peer reviewers. The editors of World Journal of Emergency Surgery and BioMed Central would like to show our appreciation by thanking the following people for their assistance reviewing manuscripts for the journal in 2013.